2022
DOI: 10.31557/apjcb.2022.7.1.21-27
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Values of PTEN Expression in Functional and Pathological Endometrial Biopsies

Abstract: Background: Endometrial carcinoma is the most common gynecological malignancy in developed countries. About 80% of endometrial carcinomas are preceded by atypical endometrial hyperplasia. PTEN is a tumor suppressor gene involved in many vital intracellular biological processes. PTEN is altered in more than 45% of endometrial carcinomas. The aim of this study was to evaluate the value immunohistochemical expression of PTEN in normal, hyperplastic and neoplastic endometrial tissues. Methods: Ninety-two endometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…However, Sarmadi et al [ 8 ] and Sal et al [ 22 ] reported a loss of PTEN expression slightly less (52% and 61%) in cases of EEC than in the present study. Although Allithy et al [ 19 ] found that none of the EEC showed strong PTEN expression, a finding similar to our study. The variation in the loss of PTEN expression in various studies could be due to various stages of disease progression, different age groups, variability in the sampling, and the use of different types of antibodies (polyclonal or monoclonal).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, Sarmadi et al [ 8 ] and Sal et al [ 22 ] reported a loss of PTEN expression slightly less (52% and 61%) in cases of EEC than in the present study. Although Allithy et al [ 19 ] found that none of the EEC showed strong PTEN expression, a finding similar to our study. The variation in the loss of PTEN expression in various studies could be due to various stages of disease progression, different age groups, variability in the sampling, and the use of different types of antibodies (polyclonal or monoclonal).…”
Section: Discussionsupporting
confidence: 91%
“…Erkanli et al [ 18 ] reported a less homogenous pattern with a few scattered PTEN null glands interposed among PTEN-positive glands in proliferative endometrium. However, other studies did not observe a loss of PTEN expression in hyperplasia without atypia [ 18 , 19 ]. Aguilar et al [ 20 ] observed aberrant PTEN expression in 50.5% of endometrial hyperplasia cases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation